2017
DOI: 10.1016/j.abb.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Probing the orientation of inhibitor and epoxy-eicosatrienoic acid binding in the active site of soluble epoxide hydrolase

Abstract: Soluble epoxide hydrolase (sEH) is an important therapeutic target of many diseases, such as chronic obstructive pulmonary disease (COPD) and diabetic neuropathic pain. It acts by hydrolyzing and thus regulating specific bioactive long chain polyunsaturated fatty acid epoxides (lcPUFA), like epoxyeicosatrienoic acids (EETs). To better predict which epoxides could be hydrolyzed by sEH, one needs to dissect the important factors and structural requirements that govern the binding of the substrates to sEH. This k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…The protein soluble epoxide hydrolase (sEH) is found in most mammalian tissues and catalyzes the conversion of epoxyeicosatrienoic acid (EETs) to dihydroxyeicosatrienoic acids (DHET) . It plays a physiological role in blood pressure, anti-inflammation, neuroprotection, and cardioprotection, and as well as being a target for treating chronic obstructive pulmonary diseases (COPD), atrial fibrillation, and diabetic neuropathic pain, it has had many drugs in clinical trials . The binding site of sEH [see Figure (C)] is large and deeply buried .…”
Section: Methodsmentioning
confidence: 99%
“…The protein soluble epoxide hydrolase (sEH) is found in most mammalian tissues and catalyzes the conversion of epoxyeicosatrienoic acid (EETs) to dihydroxyeicosatrienoic acids (DHET) . It plays a physiological role in blood pressure, anti-inflammation, neuroprotection, and cardioprotection, and as well as being a target for treating chronic obstructive pulmonary diseases (COPD), atrial fibrillation, and diabetic neuropathic pain, it has had many drugs in clinical trials . The binding site of sEH [see Figure (C)] is large and deeply buried .…”
Section: Methodsmentioning
confidence: 99%
“…12 This observation was further supported from SAR studies (EC5019 vs EC5023 in Table 1). 5,19 Also, Lee et al revealed that the binding pocket of sEH is promiscuous, 30 and the left side of the pocket can tolerate chemical structures of various sizes. 31 The tunnel appears to breathe or even open to accept bulky groups.…”
Section: ■ Biochemcal Mechanism Of Actionmentioning
confidence: 99%
“…The protonation state of the catalytic residue His374 was predicted to be protonated (positively charged). His374 is of particular importance as it lies between Asp192 and Asp348, and it has been previously shown that the protonated form is required for the stability of the complex. ,,, PROPKA suggests that most of the remaining histidine residues in both the WT and LW202 proteins should be deprotonated (neutral); for some, the appropriate protonation state is unclear. We have therefore generated complexes for both WT and LW202 where all histidine residues, with the exception of the protonated His374, are either positively charged or neutral.…”
Section: Methodsmentioning
confidence: 99%